2020
DOI: 10.1536/ihj.19-173
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Percutaneous Occlusion of Atrial Septal Defect on Left Atrial Function Evaluated Using 2D Speckle Tracking Echocardiography

Abstract: Percutaneous occlusion of atrial septal defect (ASD) has recently become a standard therapeutic strategy, but little is known about left atrial (LA) function thereafter. The present study aimed to determine LA function in 43 children with ASD and 13 controls based on LA strain measured by two-dimensional echocardiographic speckle tracking (2DE-ST). Among these children, 12 underwent surgery (ASD-S), 31 had device closure (ASD-D), and 13 were included as controls. LA strain was significantly decreased after ASD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
1
14
1
Order By: Relevance
“…These results imply that ASD occlusion devices adversely affect LA function and may be important in choosing other treatment strategies. Depression of LA function was detected by speckle tracking in adult patients immediately after device implantation, but this resolved by one month after intervention [15,16]. It is unknown if the changes in LA shape that we observed after ASD device closure impact the lives of young patients.…”
Section: Discussionmentioning
confidence: 85%
“…These results imply that ASD occlusion devices adversely affect LA function and may be important in choosing other treatment strategies. Depression of LA function was detected by speckle tracking in adult patients immediately after device implantation, but this resolved by one month after intervention [15,16]. It is unknown if the changes in LA shape that we observed after ASD device closure impact the lives of young patients.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, after percutaneous device closure, LA reservoir function was not different from that of the normal control group. Conversely, Suzuki et al 21) and Boyd et al 19) reported that immediately after treatment, the reservoir function was preserved in the surgical group and decreased in the percutaneous device group compared to controls. This discrepancy may originate from differences in the length of the follow-up period after treatment between the 2 studies.…”
Section: Discussionmentioning
confidence: 94%
“…They reported no difference in reservoir function, improved conduit function, and decreased contraction function 1 and 6 months after treatment when compared to LA functioning before the procedure. Suzuki et al 21) compared LA function before and after surgical or percutaneous device closure in a study of 43 children. In the surgical closure group, the strain value of the LA lateral wall did not change; however, in the device group, the strain value of the LA lateral wall immediately after the procedure was decreased, and the strain value was inversely correlated with the size of the device used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography is the most used method for evaluating cardiac function and two-dimensional speckle tracking imaging (2D-STI) has been widely used in the evaluation of cardiovascular disease. As a relatively new method to evaluate cardiac function, 2D-STI not only eliminates the dependence of tissue Doppler on the angle of the sound beam but is also not interfered with by the traction of the surrounding myocardium and heart movement (8,9). However, the spatial conformation of the atria and ventricles are not a regular geometric shape (10) and the results of two-dimensional Doppler ultrasound measurement are prone to errors (11).…”
Section: Introductionmentioning
confidence: 99%